Developmental variability channels mouse molar evolution - Hayden, Luke; Lochovska, Katerina; Sémon, Marie; Renaud, Sabrina; Delignette-Muller, Marie-Laure; Vilcot, Maurine; Peterkova, Renata; Hovorakova, Maria; Pantalacci, Sophie (eLife, 2020)
Do developmental systems preferentially produce certain types of variation that orient phenotypic evolution along preferred directions? At different scales, from the intra-population to the interspecific, the murine first upper molar shows repeated anterior elongation. Using a novel quantitative approach to compare the development of two mouse strains with short or long molars, we identified temporal, spatial and functional differences in tooth signaling center activity, that arise from differential tuning of the activation-inhibition mechanisms underlying tooth patterning. By tracing their fate, we could explain why only the upper first molar reacts via elongation of its anterior part. Despite a lack of genetic variation, individuals of the elongated strain varied in tooth length and the temporal dynamics of their signaling centers, highlighting the intrinsic instability of the upper molar developmental system. Collectively, these results reveal the variational properties of murine molar development that drive morphological evolution along a line of least resistance.
Keywords: Tooth Eruption; embryo savčí; fenotyp; Male; Phenotype; developmental biology; developmental constraint; rodent; molar; Molar; evolutionary biology; Pregnancy; signální transdukce; těhotenství; mouse; Embryo, Mammalian; biologická evoluce; mužské pohlaví; Signal Transduction; prořezávání zubů; Animals; line of least resistance; evo-devo; ženské pohlaví; moláry; Biological Evolution; zvířata; myši; Mice; Female; biologická variabilita populace; Biological Variation, Population